2013
DOI: 10.1002/jmv.23798
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of HBV “S” antigen genetic diversity in Iranian blood donors: A nationwide study

Abstract: The genetic diversity of the HBV S gene has a significant impact on the prophylaxis and treatment of hepatitis B infection. The effect of selective pressure on this genetic alteration has not yet been studied in Iranian blood donors. To explore HBV evolution and to analyze the effects and patterns of hepatitis B surface antigen (HBsAg) mutations on blood screening assays, 358 Iranian blood donors diagnosed as asymptomatic HBV carriers were enrolled in this nationwide study. Large S and partial S genes were amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
(102 reference statements)
4
20
0
1
Order By: Relevance
“…Subtype adw2 was similarly thought to be exclusively of genotype A but was also discovered in subgenotype D1 strains [Veazjalali et al, ; Yousif and Kramvis, ]. Even though none of the strains in this study were of subtype adw2 , this particular subtype has been identified together with subgenotype D1 in our most recent study among blood donor isolates in Iran [Pourkarim et al, ] as well as in other studies [Veazjalali et al, ; Garmiri et al, ]. In a previous study, due to a mutation detected at serine‐127, one untypable subtype strain was detected in genotype D1 strains isolated from HBV carriers living in central, northern, and western Iran [Mohebbi et al, ].…”
Section: Discussionsupporting
confidence: 58%
“…Subtype adw2 was similarly thought to be exclusively of genotype A but was also discovered in subgenotype D1 strains [Veazjalali et al, ; Yousif and Kramvis, ]. Even though none of the strains in this study were of subtype adw2 , this particular subtype has been identified together with subgenotype D1 in our most recent study among blood donor isolates in Iran [Pourkarim et al, ] as well as in other studies [Veazjalali et al, ; Garmiri et al, ]. In a previous study, due to a mutation detected at serine‐127, one untypable subtype strain was detected in genotype D1 strains isolated from HBV carriers living in central, northern, and western Iran [Mohebbi et al, ].…”
Section: Discussionsupporting
confidence: 58%
“…Twenty percent of the acute strains harbored variation within the HBsAg, whereas more than half of the chronic strains (53%) harbored variation within the HBsAg. Other studies have shown similar percentages, ranging from 40% to 55% variation, which were mostly among chronic GtD strains . The low diversity among GtA acute strains suggests that the transmission of GtA is sustained within the MSM community in The Netherlands and that there is little transmission from chronic cases leading to new infections.…”
Section: Discussionmentioning
confidence: 60%
“…An additional substitution of interest was the surface gene nonsynonymous mutation that resulted in S C69* (data not shown). This amino acid change was observed at T1 (89%) and T3 (97%) but at a much lower rate (13%) at T2 and would result in the production of a truncated S protein, which has been associated with false-negative HBsAg detection in diagnostic serological assays (40). The corresponding change in the overlapping P ORF was rtS78T (Fig.…”
Section: Resultsmentioning
confidence: 97%